2021
DOI: 10.1099/mgen.0.000738
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile strain-dependent and strain-independent adaptations to a microaerobic environment

Abstract: Clostridioides difficile (formerly Clostridium difficile ) colonizes the gastrointestinal tract following disruption of the microbiota and can initiate a spectrum of clinical manifestations ranging from asymptomatic to life-threatening colitis. Following antibiotic treatment, luminal oxygen concentrations increase, exposing gut microbes to potentially toxic reactive oxygen species. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…We mined published C. difficile RNA-sequencing data ( 50 , 51 ) and observed expression from all intron and IS605 elements, though precise mapping to predicted ωRNA regions was confounded by their highly repetitive nature and the sequencing method ( fig. S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…We mined published C. difficile RNA-sequencing data ( 50 , 51 ) and observed expression from all intron and IS605 elements, though precise mapping to predicted ωRNA regions was confounded by their highly repetitive nature and the sequencing method ( fig. S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that C. difficile fhuB was upregulated during hamster infection ( 4 ) and growth under microaerophilic conditions (33) suggesting the FhuDBGC transporter may be important during colonization. To determine the impact of the ΔfhuDBGC mutation on colonization, we used the cefoperazone mouse model of C. difficile infection (CDI) (17).…”
Section: Resultsmentioning
confidence: 99%
“…The WT and complemented strains likely succumb to the effects of superoxide before the stress response genes are activated. However, sodA in C. difficile has been associated only with spore coat formation or maturation ( 39 ) and not with aerobic stress management ( 48 , 49 ). Instead σ B -associated desulfoferrodoxin, reverse rubrerythrins, and NADH-rubredoxin reductases have been described as remedial agents ( 17 ).…”
Section: Discussionmentioning
confidence: 99%